‘Out-off-the map’. Finding places of marginalization and vulnerability in Lisbon Metropolitan Area - Santos, S.; Ferreiro, Maria de Fátima; Ramos, Isabel; Gonçalves, Alexandre (AESOP (Association of European Schools of Planning) 2018 Annual Congress, Making Space for Hope, 2018)
In a globalized world, inequality, socio-economic marginalization or vulnerability are not geographically confined. They exist beyond official borders, whether they are local, regional, national or international. Metropolitan areas, especially diverse and contrasted concerning uses, activities or livelihoods, are therefore spaces with a heterogeneous distribution of social and economic opportunities or vulnerabilities. Lisbon Metropolitan Area (LMA) is no exception. With a population of 2,8 million inhabitants, it’s the most competitive economic centre of the country, with increasing global integration. Its geography, a blend of ‘leading’ territories co-existing with ‘lagging territories’, where problems such as lack of land use planning, landscape disqualification, economic disadvantages, or social-spatial exclusion persist, it’s not easily captured by the official data collected and made public. This paper will present research achievements related to an iterative process of clustering, ranking and spatializing (ArcGIS) ‘edge-values’ of collected data (Census, Land Use Maps, Other Institutional sources) at distinct desegregation levels, that allowed the identification of territorial typologies, places and communities in LMA, where extreme processes of socio-economic, institutional or environmental marginalization occur. It will also discuss the role of this methodology in testing the way statistical information and mapping is being produced, used and communicated and how it may influence urban planning decisions, policy options or even knowledge production. If territorial analysis and action is exclusively driven by indicators average-values and administrative borders, it may be persistently pushing off-the-map, pockets of disadvantaged geographies, weighing statistical relevance against social urgency and hindering the path towards a more inclusive and hopeful city.